Spectrophotometric determination of the stability constant of vanadium(v)-p-chloro-N-phenyl-p-chlorobenzo- hydroxamic acid complex - Abualreish, Mustafa; Al msiedeen, A.M. (International Journal of Advanced Chemistry, 2014)
The stability constant of the complex vanadium(v) p-chloro-N-Phenyl-p-chlorobenzohydroxamic acid was determined spectropho-tometrically. The ligand p-chloro-N-phenyl-p-chloro-benzohydroxamic acid abbreviated in this paper as PCNPPCBHA was synthesized by the coupling of equimolar solutions of p-chlorobenzoyl chloride and freshly prepared p-chloro-ß-phenyl hydroxylamine; in which the later was prepared by the reduction of p-chloronitrobenzene with zinc powder. The pH at maximum extraction of the ligand PCNPPCBHA to the metal vanadium(v) and the ratio of the ligand: metal , were determined. Keywords : Spectrophotometric determination , Vanadium(V) , p - chloro - N - phenyl - p - chloro-benzohydroxamic acid.